Program Layanan Pengembangan Konsep Diri Dalam Membentuk Kesadaran Disiplin Belajar Siswa Di Sekolah - Siti Muzaro’ah (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The sight of students being given sanctions for not doing homework or schoolwork, not coming on time, rarely using free time in class to study, cheating on exams, leaving class hours at will on the grounds of going to the UKS or going to the bathroom is a common phenomenon in various schools. This indicates students' weak discipline in learning due to their lack of motivation to learn. This research is aimed at describing efforts to increase students' learning awareness through positive self-concept development service programs. The research results found; 1) The level of awareness of students' learning discipline is in line with their learning motivation and positive self-understanding; 2) A positive self-concept development service program that is practical, flexible and interesting and in harmony with student psychology and can be obtained by students anytime and anywhere; 3) The information service program for developing positive self-concept is oriented towards motivating students' learning on an extrinsic basis aimed at fostering intrinsic learning motivation so that it can raise students' awareness of the importance of learning to realize the goals they want to achieve and being disciplined in learning; 4) Developing students' positive self-concept with a focused goal of motivating interest and action, providing self-information and instructions can give students experience in understanding themselves by honing their positive self-concept, so that learning is a necessity, not an obligation.